Effect of lemon grass (Cymbopogen citratus) extract on seed health of rice - Rahman, MZ; Ali, M Ayub; Hossain, MS; Monsur, MA; Zaman, MZ (Bangladesh Rice Journal, 2014)
Lemon grass extract was evaluated in different dilutions on rice seed health in laboratory and net house experiments. The objectives were to investigate the effect of lemon grass extract on seed-borne pathogen of rice and seedling vigour. Four treatments as 1:1, 1:2, 1:3 dilution of lemon grass extract including a control were studied. Lemon grass extract at 1:1 dilution showed highest germination and vigour index of rice seed and seedlings. It was also found most effective in controlling seed borne fungi of rice. The fungi Bipolaris oryzae, Alternaria padwickii, Curvularia lunata, Fusarium moniliforme, Aspergillus and Penicillium spp. were controlled effectively by soaking seeds in the extract of lemon grass at 1:1 dilution for 6 hours. DOI: http://dx.doi.org/10.3329/brj.v17i1-2.20904 Bangladesh Rice j. 2013, 17(1&2): 105-108